The Role of Bitter-Tasting Substances in Salivation and Swallowing: Results of the Pilot Study - Ekaterina Oganesiants; Varuzhan Sarkisyan; Anastasiya Bilyalova; Vasily Isakov; Alla Kochetkova (Foods)
The aim of this study was to investigate the effects of caffeine, vanillin, and epigallocatechin gallate on salivation and swallowing and to find ways to correct their negative effects. Solutions of these substances with an equivalent intensity of bitter taste were compared for this purpose. To compensate for their effect, solutions of adenosine monophosphate, saliva substitute, and their combination were used. The results of the sialometric and surface electromyographic analyses demonstrate that all of the bitter substances studied exert a significant influence on the physiology of salivation and swallowing while exhibiting distinct modes of action. Caffeine has been shown to increase the area under the swallowing electromyographic curve, which is indicative of an increase in maximal amplitude. Epigallocatechin gallate has been linked to a reduction in salivation rate, an increase in duration, and a decrease in maximal intensity of the sEMG curve. Vanillin is demonstrated to reduce the area under the swallowing electromyographic curve due to a decline in both duration and maximal intensity. The addition of adenosine monophosphate to solutions of all substances under study resulted in a convergence of the salivary secretion and swallowing profile toward a profile that is characteristic of water. The findings can be utilized to modify the physiological responses to bitter-tasting substances when developing novel food formulations.